The Model of Electrical Service of Provincial Electricity Authority : A Case Study of Ban Phai Municipality, Ban Phai District, Khon Kaen Province. - สันหนองเมือง ปรีชา (Journal of Graduate MCU KhonKaen Campus, 2016)
This study aims to explore the issues of consumer’s needs and the favorable forms of electrical providing service of the Provincial Electricity Authority and propose the model of electrical service of the Provincial Electricity Authority of Ban Phai District as a case study of Ban Phai Municipality, Ban Phai District, Khon Kaen Province. The major problems of electrical service are as follows: 1) The personnel: there is a need to increase the number of staff to provide the service adequately and to have service-mind for all the time; 2) the process: the services in troubleshooting power failure/outage, applying new registration, moving/installing meter, and paying for the electricity bills should become faster; 3) the location and environment: security in the office is required and the signs that are easy to understand where to get service points should be provided; 4) the quality of services: the counter services for each type of service should be separated; 5) the price and the cost of the service: the fee of electricity should be reduced; and 6) the promotion: educating and informing consumers about the news through a number of media e.g. internet, radio, television, brochures should be constantly and thoroughly maintained. According to the model of electrical services of Provincial Electricity Authority, it is proposed that the executives and staff of the Provincial Electricity Authority must focus on the services in all areas including human resources, processes, location and environment, quality of service, price and cost of the service, promotion and information to the consumer.